A Pacific Human Rights Mechanism: Specific Challenges and Requirements - Hay, Kathryn (Victoria University of Wellington Law Review, 2009)
This article examines several key challenges that face Pacific leaders and other stakeholders in their consideration of a regional human rights mechanism, including the important question whether a regional mechanism is at all necessary. The article draws mainly on material from six interviews with participants from the Pacific region working in government and academia to examine those key challenges. The article closes with some suggested requirements in order for a regional human rights mechanism to be effective in the Pacific.